The Effect of Agro-Industrial Waste Mixtures on Productivity and Nutrient Content of Black Soldier Fly Larvae (hermetia illucens) - Arifki, Muhammad Primo; Tafsin, Ma'ruf; Fatimah (TALENTA Publisher, Universitas Sumatera Utara, 2024)
The feed media content plays an essential role in the growth of BSF larvae; appropriate feed content will provide optimal growth for BSF larvae. Agricultural industrial waste contains high levels of protein, fiber, and carbohydrates, which play an essential role in the growth and nutrition of BSF larvae. This study aims to determine the effect of providing agricultural waste as feed on the relative growth rate, rate of degradation of organic waste, and the nutritional content of BSF biomass. This research is an experimental study using various levels of experiments from the Laboratory of Standardization and Industrial Services Center in Medan, Indonesia, using the SNI 01-2891-1992 method, which consisted of ash content, carbohydrates, total fat, protein, and crude fiber. The results showed that the feed media's protein content would be more easily digested than the more complex carbohydrate and fiber content. It will increase protein content in feed media, giving a higher growth rate in larva BSF. The feed media with the highest protein content causes the feed media to be consumed more quickly, producing lower unconsumed feed residue and showing the highest degradation rate. The high protein content in the feed media can increase Proteobacteria bacteria and increase the protein bioconversion process in the intestines of BSF larvae.